Compact spin-valley-locked perovskite emission - Chen, Yang (2023)
Circularly polarized light sources with free-space directional emission play a key role in chiroptics1, spintronics2, valleytronics3 and asymmetric photocatalysis4. However, conventional approaches fail to simultaneously realize pure circular polarization, high directionality and large emission angles in a compact emitter. Metal-halide perovskite semiconductors are promising light emitters5-8, but the absence of an intrinsic spin-locking mechanism results in poor emission chirality. Further, device integration has undermined the efficiency and directionality of perovskite chiral emitters. Here we realize compact spin-valley-locked perovskite emitting metasurfaces where spin-dependent geometric phases are imparted into bound states in the continuum via Brillouin zone folding, and thus, photons with different spins are selectively addressed to opposite valleys. Employing this approach, chiral purity of 0.91 and emission angle of 41.0° are simultaneously achieved, with a beam divergence angle of 1.6°. With this approach, we envisage the realization of chiral light-emitting diodes, as well as the on-chip generation of entangled photon pairs.